Unravelling the link between periodontitis and abdominal aortic calcification in the US adult population: a cross-sectional study based on the NHANES 2013–2014. Issue 3 (15th March 2023) - Kadier, Kaisaierjiang; Abulizi, Anniwaer; Ainiwaer, Aikeliyaer; Rehemuding, Rena; Ma, Xiang; Ma, Yi-Tong
Abstract : Objective: We aimed to explore the association between periodontitis and abdominal aortic calcification (AAC) among a nationally representative sample of US adults. Design: Cross- sectional study. Setting: The National Health and Nutrition Examination Survey (2013–2014). Participants: A total of 2149 participants aged 40 years or older who have complete information for periodontitis and AAC assessment test were included in this study. Primary and secondary outcome measures: AAC scores can be accurately identified on lateral spine images obtained by dual-energy X-ray absorptiometry, and both the AAC-24 and AAC-8 semiquantitative scoring tools were used for AAC evaluation. Linear regression analysis was used to investigate the relationship between periodontitis and the AAC-8 and AAC-24 scores. Multivariate logistic regression models and reported ORs were used to examine the relationship between periodontitis and AAC. Results: The prevalence of severe periodontitis combined with severe AAC was 8.49%–8.54%. According to the AAC-8 and AAC-24 score classifications, patients with severe periodontitis had higher odds of severe AAC (AAC-8 score ≥3: (OR: 2.53; 95% CI 1.04 to 6.17) and AAC-24 score >6: (OR: 3.60; 95% CI 1.48 to 8.78)). A positive association between mild–moderate periodontitis and severe AAC was found only when the AAC-24 score was applied (OR: 2.25; 95% CI 1.24 to 4.06). In the subgroup analyses, the likelihood ratio test showed no multiplicative interaction (all p value for interaction >0.05). Conclusions: The findings showed that periodontitis is associated with an increased risk of severe AAC in the US population aged 40 years and older; this requires further large-scale prospective studies for confirmation.